2006
DOI: 10.1007/s10554-006-9196-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial calcification and subendocardial fatty replacement of the left ventricle following myocardial infarction

Abstract: We report a 70 years old man with old myocardial infarction of the anteroseptal wall. He had an acute anterior myocardial infarction ten years ago and coronary angiography showed a total occlusion of the left middle anterior descending coronary artery. He underwent a multidetector cardiac computed tomography for rule out another coronary stenosis before the surgery of a postrenal aortic aneurysm. The unenhanced computed tomography image realized for the quantification of the coronary calcium reveals a low-atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…20 ). This finding is confirmed also in LV aneurysms that developed from myocardial infarction [ 177 ]. Other entities that show abnormal myocardial fat include arrhythmogenic right ventricular cardiomyopathy or dysplasia (ARVC), cardiac lipoma, LHIAS, tuberous sclerosis, complex tuberculosis, dilated cardiomyopathy, and muscular dystrophy [ 176 ].…”
Section: Extra-myocardial Findingsupporting
confidence: 55%
“…20 ). This finding is confirmed also in LV aneurysms that developed from myocardial infarction [ 177 ]. Other entities that show abnormal myocardial fat include arrhythmogenic right ventricular cardiomyopathy or dysplasia (ARVC), cardiac lipoma, LHIAS, tuberous sclerosis, complex tuberculosis, dilated cardiomyopathy, and muscular dystrophy [ 176 ].…”
Section: Extra-myocardial Findingsupporting
confidence: 55%
“…Fat-water–separated late enhancement imaging has recently been introduced [11••, 12] and may be used be used to directly image fat in chronic MI. A number of cardiac CT studies have also reported the presence of fat associated with chronic MI [46]. The measurement of fibrofatty infiltration in chronic MI by imaging studies is relatively new.…”
Section: Ischemic Cardiomyopathymentioning
confidence: 99%